Soil Stabilization with Rice Husk Ash and Lime Sludge (International Journal of Innovative Research in Engineering & Management, 2022)
Soil with low bearing and shear strength  requires stabilization to improve its engineering properties  and make it suitable for construction. In this study, rice  husk and lime sludge are used for stabilization because  they are locally available, reducing the amount of waste  disposed of to the environment. The main objective of this  study is to determine the optimum percentage rice husk and  lime sludge for soil stabilization and to assess the effects  of Rice husk ash and lime sludge percentage on the  Atterberg limits. Apart from that also to assess the effects  of Rice husk ash and lime sludge percentage on California  Bearing Ratio and on maximum dry density and optimum  moisture content. In this study, RHA and Lime sludge was added to the soil  samples and various experiments were conducted on them  to understand the effect the addition of these admixtures  has on the soil. The RHA was added in percentages of 5,10,  15 and 20 %. The lime sludge was added in the percentages  of 5,10,15 and 20 %. The test conducted on these samples  were Liquid limit, plastic limit, standard proctor and CBR  test. The results of these experiments showed that the  addition of these admixtures caused the liquid limit of soil  to decrease. The addition of RHA and Lime sludge caused  the plastic limit to increase. The OMC increased as the  percentage of RHA and lime sludge was increased in the  samples. The OMC increased by 33 % for addition of 20  % RHA. The OMC increased by 37 % for addition of 20  % lime sludge. The MDD decreased as the percentage of  RHA and lime sludge was increased in the samples. The  MDD decreased by 23 % for addition of 20 % RHA. The  MDD decreased by 25 % for addition of 20 % lime sludge. The CBR increased by 149 % for 20 % addition of RHA to  the sample. The CBR increased by 137 % for 20 % addition  of Lime Sludge to the sample. The samples with RHA  showed greater improvement in strength compared with  Lime Sludge.
Keywords: Soil Stabilization; Waste Reduction; California Bearing Ratio (CBR); Unconfined Compressive Strength (UCS); Atterberg Limits